Landscape processes underpinning bird persistence and avian-mediated pest control in fragmented landscapes - Boesing, Andrea Larissa (2016)
The influence of habitat loss on biodiversity is related to a set of non-linear processes, which strongly affect isolation and connectivity and determine both extinction and colonization rates. Landscape changes due anthropogenic disturbances are driving not only species loss per se, but also loss of functions performed by those species, which could have important impacts on the provision of ecosystem services and ecosystem function. The objective of this dissertation is to move beyond our current understanding about landscape processes underpinning bird persistence and avian-mediated pest control in fragmented landscapes. In chapter 1, we systematically review the empirical evidence of landscape structure effects on avian-mediated pest control in agricultural systems worldwide in order to point out the main landscape processes underpinning ecosystem service provision and gaps in knowledge where research efforts should be focused. We have found 226 bird species that provide pest regulation worldwide, and a substantial proportion of those are native habitat-dependent species in tropical systems. Moreover, more heterogeneous landscapes, increased habitat amount, and decreased isolation among patches are positively associated with increased avian-mediated pest control rates. Then, using bird data collected in fragmented landscapes in the Brazilian Atlantic forest, in chapter 2 we test for community-level extinction thresholds across a range of biodiversity indices (taxonomic, functional, and phylogenetic diversity) in order to evaluate how much habitat is need to maintain sustainable ecosystem functioning and ecosystem resilience, and how matrix composition might affect these thresholds. In general, we have found that more permeable matrices are able to postpone species loss in fragmented landscapes. However, since habitat loss reaches 20% of habitat remaining, all aspects of biodiversity are compromised. Finally, in chapter 3 we investigate the cross-habitat spillover process - one of the main processes regulating avian-mediated pest control in tropical regions. Matrix composition is a key factor in facilitating species movement into matrices, as 24% of the species pool can spill over into coffee plantations, while spillover into pasture is nearly non-existent. Moreover, the interaction between forest cover and edge density is an important predictor of spillover when habitat amount is low. Our results suggest that landscape configuration and matrix composition should be considered when planning agricultural landscapes in order to ensure long-term persistence of biodiversity and ecosystem services provision